Suppressing piezoelectric screening effect at atomic scale for enhanced piezoelectricity. (January 2023) - Sun, Yue; Shen, Sophia; Deng, Weili; Tian, Guo; Xiong, Da; Zhang, Hongrui; Yang, Tao; Wang, Shenglong; Chen, Jun; Yang, Weiqing
Abstract: Zinc oxide (ZnO) is one of the most popular piezoelectric materials since it is non-toxic and environmentally friendly. However, its widespread adoption is largely hindered by its lower piezoelectricity. Herein, we report a generalizable approach to improving the piezoelectricity of ZnO via suppressing its piezoelectric screening effect at an atomic scale via rare earth (RE) ions doping. The developed Y 3+ : ZnO demonstrates a 91.8%-dropped carrier concentration and a 53.8%-increased surface piezoelectric response compared to undoped ZnO. Combining work function from Kelvin probe force microscopy (KPFM) and piezoelectric response distribution from piezoresponse force microscopy (PFM), this work reveals that the RE ion doping strategy can indeed suppress the piezoelectric screening effect and thus greatly enhance the piezoelectricity. The contribution of the atomic suppression strategy of screening effect to the community is two-fold: 1. it provides a fundamental understanding of intrinsic piezoelectric mechanism in the ZnO. 2. it could be extended and adapted to other piezoelectric materials. Overall, this work opens a new strategy for piezoelectric enhancement and applicative piezoelectrics. Graphical Abstract: The graphic abstract accurately summarizes the main content of this work: The widening of bandgap caused by various rare earth ions doping ZnO reveals the suppression of doping on screening effect. ga1 Highlights: A new perspective to understand the huge piezoelectricity enhancement of RE 3+ doping ZnO. Confirming that RE 3+ doping can suppress potential screening effect of ZnO at an atomic scale. The low-temperature method of preparing RE 3+ : ZnO providing more possibilities for stretchable piezoelectrics.